Nox1/4 inhibition exacerbates age dependent perivascular inflammation and fibrosis in a model of spontaneous hypertension. (November 2020) - Nosalski, R.; Mikolajczyk, T.; Siedlinski, M.; Saju, B.; Koziol, J.; Maffia, P.; Guzik, T.J.
Graphical abstract: Abstract: Hypertension is associated with oxidative stress and perivascular inflammation, critical contributors to perivascular fibrosis and accelerated vascular ageing. Oxidative stress can promote vascular inflammation, creating options for potential use of NADPH oxidase inhibitors in pharmacological targeting of perivascular inflammation and its consequences. Accordingly, we characterized age-related changes in oxidative stress and immune cell infiltration in normotensive (WKY) and spontaneously hypertensive rats (SHRs). Subsequently, we used pharmacological inhibitors of Nox1 (ML171) and Nox1/Nox4 (GKT137831; 60 mg/kg), to modulate NADPH oxidase activity at the early stage of spontaneous hypertension and investigated their effects on perivascular inflammation and fibrosis. Results: Ageing was associated with a progressive increase of blood pressure as well as an elevation of the total number of leukocytes, macrophages and NK cells infiltrating perivascular adipose tissue (PVAT) in SHRs but not in WKY. At 1 month of age, when blood pressure was not yet different, only perivascular NK cells were significantly higher in SHR. Spontaneous hypertension was also accompanied by the higher perivascular T cell accumulation, although this increase was age independent. Aortic Nox1 and Nox2 mRNA expression increased with age only in SHR but not in WKY, while age-related increase of Nox4 mRNA in the vessels has been observed in both groups, it was more pronounced in SHRs. At early stage of hypertension (3-months) the most pronounced differences were observed in Nox1 and Nox4. Surprisingly, GKT137831, dual inhibitor of Nox1/4, therapy increased both blood pressure and perivascular macrophage infiltration. Mechanistically, this was linked to increased expression of proinflammatory chemokines expression (CCL2 and CCL5) in PVAT. This inflammatory response translated to increased perivascular fibrosis. This effect was likely Nox4 dependent as the Nox1 inhibitor ML171 did not affect the development of spontaneous hypertension, perivascular macrophage accumulation, chemokine expression nor adventitial collagen deposition. In summary, spontaneous hypertension promotes ageing-associated perivascular inflammation which is exacerbated by Nox4 but not Nox1 pharmacological inhibition.